ATTITUDE TOWARDS HEALTH AS ONE OF THE MOST SIGNIFICANT FORMATIVE PSYCHOLOGICAL FACTORS - Reshta, V.M.; Yeroshenko, G.A.; Lysachenko, O.D.; Klymach, T.N. (World of Medicine and Biology, 2015)
As a result of empirical research it can be concluded, students and high school students especially appreciate the morality, ethics, culture and environmental values as they take second place. With regard to their own health students defined the system of individual electoral links with a person different phenomena of reality, contribute to or, conversely, threaten the health of people, as well as certain individual evaluation of his mental or physical condition. There are age dynamics of the importance of health. Young people, of course, relate to the issue of health as something important, but abstract, such that it has no direct relation to him. If they pay attention to the health, it is mainly its physical component. In their understanding of the psychological and social health do not occupy a proper place in the category of values. The age and health of self-esteem are inversely related.